Student`s Understanding toward Rural Development Development after Learning from Local Visit by the Faculty of Education Souphanouvong University; During Academic Year of 2018 - 2020: https://doi.org/10.69692/SUJMRD0802142 - KHOTSAIGNOH, Saiphone; SOULIVONG, Phetsamone; SAYTHALA, Khanty; SIRIRATH, Khamphy; OUDOMSITH, Houmpheng; LIAMAHER , Yearher; VONGVILAY, Chanpheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aimed to investigate the students’ understanding toward rural development after learning from local visit at rural areas by Faculty of Education Souphanouvong University, which is a subject that belongs to the political science curriculum of Faculty of Education, Souphanouvong University. The research was to gain insights regarding the understanding level by using the pretest and posttest to assess their learning progress, then compared means of those scores with the variable of their residence origins, The sampling students focused on 58 students (27 Women students included) of political science department, the instrument of this research was an objective test with multiple choice with IOC = 1.00 and difficulty level ranged between 0.40-0.86; and the reliability was of 0.84; there are two steps of assessment including of before and after local visiting with the same questionnaire The research findings revealed that 1). The students` understand about rural development policy after local visit was significant higher with the compared mean of posttest remark after local visit was significant different Sig .05, and 2). The students` understand about rural development policy after local visit compared to residence origins were not significant different.